An investigation of a Systemic Functional Linguistic approach for teaching Energy to grade 7 Natural Science and Health Education Learners: a Namibian case study - Silvanus, Secilia Tulikefo (Rhodes University, Faculty of Education, Department of Education, 2017)
Learners' general poor performance in science is a concern in science education. The literature mentions pedagogic strategies such as the use of practical activities and inclusion of indigenous knowledge, which are now acknowledged in various science curricula. In addition, many science educators and researchers are exploring innovative pedagogical approaches which may possibly help learners understand science better in order to improve their performance in the subject. Learners' poor performance in science and possible strategies for improving this, are also a concern in Namibia. The Namibian national examination results (MoE, 2010-2014) revealed that the topic of Energy is one of those in which learners perform poorly. Energy is an important scientific concept that is widely used in various disciplines and it is thus problematic when science learners struggle to make sense of the scientific description of energy and related concepts. This triggered my interest to conduct a study focusing on the topic of energy. The study involved functional recasting from Systemic Functional Linguistic theory, as an intervention during my teaching the topic of energy to English second language grade 7 Natural Science and Health Education learners. The influence of the approach was investigated through the lens of social constructivism. The interpretive paradigm was adopted in order to make meaning of the learners' experiences, during and after the intervention. Data collection instruments such as pre and post test, stimulated recall interviews, observation and learners' journals were used. A qualitative approach was used to analyze the data. The pretest and post test results showed that a noticeable shift had occurred in learners' understanding - the functional recasting teaching approach positively influenced learners' sense making of energy concepts. Sense-making of energy concepts was evident in learners' demonstrating the ability to construct and deconstruct technicality, making comprehensible output, meaningful use of gestures, scientific reasoning and asking relevant questions. The results also revealed dialogic discourse and positive attitudes as factors enabling learners' progress. The language of learning and teaching, and negative attitudes were found to be constraining factors for learners' progress. Functional recasting might be useful to science teachers and science teacher training programs as the finding for this study revealed that it enabled learners to make sense of energy concepts using scientific English. When using functional recasting, science teachers should consider the constraining factors and possibly avoid or minimize the impact.
Keywords: Uncatalogued